(untitled) (Asian Journal of Pharmaceutics (AJP), 2025)
Introduction: Lactoferrin (LF)-loaded solid lipid nanoparticles (SLNs) enhance LF’s stability, bioavailability, and targeted anticancer activity by protecting it from degradation and enabling receptor-mediated delivery to tumor cells. This nanocarrier system offers a promising strategy for effective and safe cancer prevention and therapy. Methodology: A standard curve for LF was established by measuring the absorbance of serial dilutions at 465 nm, showing linearity confirmed by a high correlation coefficient (R2 ) using linear regression analysis. The infrared spectra confirmed the presence of characteristic functional groups of LF, poloxamer, and the optimized formulation F6, indicating successful incorporation of both components without major structural alterations. LF-loaded SLNs were successfully formulated via homogenization–ultrasonication, producing nanosized particles (30–100 nm) with mannitol as a cryoprotectant during lyophilization. Results and Discussion: LF-loaded SLN formulations showed optimal entrapment efficiency (50.61–58.01%) at specific lipid and surfactant concentrations, with efficiency influenced by lipid-to-surfactant ratio and surfactant-induced surface coverage. The polydispersity index (PDI) of LF-loaded SLNs indicated narrow size distribution and good stability, with particle size and PDI increasing alongside glyceryl behenate concentration. Zeta potential analysis using Horiba SZ-100 confirmed the stability of optimized LF-loaded SLNs, with a high surface charge preventing aggregation and ensuring uniform dispersion. In vitro release kinetics of optimized LF-loaded nanoparticles best fit the Higuchi model (r2 = 0.9619), indicating diffusion-controlled release from the lipophilic matrix. Conclusion: The study indicates that the nanocarrier system offers a viable and successful method for LF delivery in cancer treatment and prevention.